2006
DOI: 10.1007/s00520-006-0025-x
|View full text |Cite
|
Sign up to set email alerts
|

Medical decision-making of the patient in the context of the family: results of a survey

Abstract: The family plays a central role in medical decision-making. This could be shown by a survey among patients with malignant diseases and their dependents. These initial findings must be verified in a larger population. The increased inclusion of the family in the process of medical decision-making corresponds in general to the expressed will of the patients. The model of shared decision-making is favored by values which both the family and the patient have in common. Thus, a family-based decision-making theory n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 29 publications
1
45
0
2
Order By: Relevance
“…This is similar to the finding in a study of 50 patients with a malignant disease in Germany. 13 What is new in our study is that this proportion of patients did not change significantly over time after diagnosis.…”
Section: Discussionmentioning
confidence: 65%
“…This is similar to the finding in a study of 50 patients with a malignant disease in Germany. 13 What is new in our study is that this proportion of patients did not change significantly over time after diagnosis.…”
Section: Discussionmentioning
confidence: 65%
“…Family members (FMs) are usually the main source of support throughout a patient's cancer experience [1], regularly attend consultations [2,3] and are often involved in discussions about important medical decisions [4]. Our group's systematic review [5], along with a meta-analysis by Wolff and Roter [6], found that a number of quantitative studies have been conducted amongst cancer patients and FMs indicating that family involvement in the care process is complex, but mostly beneficial.…”
Section: Introductionmentioning
confidence: 97%
“…Most cancer patients (49-84%) and family caregivers (54-59%) report both preferring and experiencing some family caregiver involvement in DM [8][9][10][11][12]. However the form and extent of family involvement in DM appears to vary widely.…”
Section: Introductionmentioning
confidence: 99%
“…However the form and extent of family involvement in DM appears to vary widely. Most patients and family caregivers prefer family caregivers' involvement to be facilitative or collaborative [9,12], and this preference is reflected in practice. In a US study examining the experiences of over 5,000 patients with lung and colorectal cancer, 1.5% of the sample reported their family made important decisions on their behalf, 49.4% reported equally sharing decisions with family, 22.1% reported some family involvement, and 28.5% of patients reported little or no role for their family in DM.…”
Section: Introductionmentioning
confidence: 99%